Good Jobs in Turkey - Grun, Rebekka (World Bank, Washington, DC, 2015)
This joint study, by the World Bank and the Turkish Ministry of Development, explores the status and effects of good jobs in Turkey s current economy. After a brief account of economic events, it examines the relationship between growth and employment in Turkey, with a particular regard to the participation of different social groups in the labor market, such as women and youth. It then analyzes where jobs are being created and which activities are the most productive for the Turkish economy, and assesses if jobs have moved to more productive activities in recent years. Finally, the report proceeds to measure the impact of different types of jobs on the welfare of an entire household and on the household s relative position in the overall income distribution.